2017
DOI: 10.21608/ejar.2017.146239
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathogenicity of Fusarium Spp. Isolated From Flax Roots

Abstract: even different fungi were isolated from the necrotic root tissues of infected Flax seedlings or older plants. Samples used in isolation were randomly collected from the experimental flax plots at Giza Agricultural Research Station. Fusarium spp. were isolated most frequently comprising 41.09%, while frequencies of isolation of the other fungi ranged from 1.00 to 23.97%. Regression analysis revealed that root colonization incidence (RCI) and root colonization severity (RCS) and relationship of rootcolonizating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Once mixed, the bottles were autoclaved for 2h. The secluded inoculum was aseptically placed in the bottle and allowed to colonize on the sorghum for 2 weeks after being obtained from a one-week-old culture on PDA (Aly et al, 1996).…”
Section: Preparation Of Fungal Inoculatementioning
confidence: 99%
See 2 more Smart Citations
“…Once mixed, the bottles were autoclaved for 2h. The secluded inoculum was aseptically placed in the bottle and allowed to colonize on the sorghum for 2 weeks after being obtained from a one-week-old culture on PDA (Aly et al, 1996).…”
Section: Preparation Of Fungal Inoculatementioning
confidence: 99%
“…The only species capable of invading and killing cotton seedlings were F. oxysporum and F. moniliforme; the rest were categorized as wound parasites or saprophytes. Aly et al (1996) found Fusarium spp. in 97.7% of 88 tested samples taken from naturally infected cotton roots in various Egyptian governorates, and also documented that F. oxysporum and F. moniliforme were significant pathogens in the etiology of cotton damping-off in Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…phaseolina is widely distributed on Egyptian ground, and it is easily and frequently Late in the growth season, cotton roots were isolated. Thus, when (Aly et al, 1996) collected and assayed M. phaseolina was recovered from 37.5 percent of the samples analysed from 88 samples of infected cotton roots from 12 Egyptian governorates. However, it was not clear whether this variation represented usable resistance in a breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…F. solani isolates, on the other hand, were nearly all extremely pathogenic (Nelson et al, 1997). Fusarium was commonly isolated from damping-off-infected cotton seedlings in cotton (Aly et al, 1996;El Samawaty, 1999). F. solani isolates from cotton were found to be pathogenic in 83 percent of cases (Abd-Elsalam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%